Fibrillar extracellular matrix produced by pericyte-like cells facilitates glioma cell dissemination - Vymola, Petr; Garcia-Borja, Elena; Cervenka, Jakub; Balaziova, Eva; Vymolova, Barbora; Veprkova, Jana; Vodicka, Petr; Skalnikova, Helena; Tomas, Robert; Netuka, David; Busek, Petr; Sedo, Aleksi (Brain pathology, 2024)
Gliomagenesis induces profound changes in the composition of the extracellular matrix (ECM) of the brain. In this study, we identified a cellular population responsible for the increased deposition of collagen I and fibronectin in glioblastoma. Elevated levels of the fibrillar proteins collagen I and fibronectin were associated with the expression of fibroblast activation protein (FAP), which is predominantly found in pericyte-like cells in glioblastoma. FAP+ pericyte-like cells were present in regions rich in collagen I and fibronectin in biopsy material and produced substantially more collagen I and fibronectin in vitro compared to other cell types found in the GBM microenvironment. Using mass spectrometry, we demonstrated that 3D matrices produced by FAP+ pericyte-like cells are rich in collagen I and fibronectin and contain several basement membrane proteins. This expression pattern differed markedly from glioma cells. Finally, we have shown that ECM produced by FAP+ pericyte-like cells enhances the migration of glioma cells including glioma stem-like cells, promotes their adhesion, and activates focal adhesion kinase (FAK) signaling. Taken together, our findings establish FAP+ pericyte-like cells as crucial producers of a complex ECM rich in collagen I and fibronectin, facilitating the dissemination of glioma cells through FAK activation.
Keywords: Pericytes; kolagen typu I; gliom; serinové endopeptidasy; Cell Line, Tumor; Serine Endopeptidases; Fibronectins; endopeptidasy; nádorové mikroprostředí; nádory mozku; lidé; membránové proteiny; Glioma; glioblastom; extracelulární matrix; Glioblastoma; pohyb buněk; Endopeptidases; fibronektiny; Brain Neoplasms; želatinasy; pericyty; Extracellular Matrix; Membrane Proteins; Tumor Microenvironment; Cell Movement; Collagen Type I; Gelatinases; nádorové buněčné linie; Humans